Differences in the hydroxylation pattern of flavonoids alter their chemoprotective effect against direct- and indirect-acting mutagens - Resende, Flavia A. [UNESP]; Silva Almeida, Carolina P. da [UNESP]; Vilegas, Wagner [UNESP]; Varanda, Eliana Aparecida [UNESP] (Elsevier B.V., 2014)
The antimutagenicity of ten flavonoids, differing in their hydroxylation patterns against direct-acting and indirect-acting mutagens, namely 4-nitro-o-phenylenediamine, sodium azide, mitomycin C, benzo[a]pyrene, aflatoxin B-1 and 2-aminofluorene, were compared with the aim of investigating how the hydroxyl groups in their structures govern the biological activity of flavonoids, by the Ames test, with Salmonella typhimurium strains TA98, TA100 and TA102. The flavonoids tested were: quercetin, kaempferol, luteolin, fisetin, chrysin, galangin, flavone, 3-hydroxyflavone, 5-hydroxyflavone and 7-hydroxyflavone. In these tests, all compounds were shown to be antimutagenic in more than one strain and various mechanisms of action were demonstrated. The results suggested that the number and position of hydroxyl groups may increase or decrease the protective effect, depending on the type and concentration of flavonoids and mutagen used. These studies contribute to clarifying the mechanisms by which these flavonoids act in protecting DNA from damage. This is required before they can be widely used. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Flavonoids; Antimutagenicity; Ames test